Water absorption and electrical resistivity of concrete with recycled concrete aggregates and fly ash. (January 2019) - Kurda, Rawaz; de Brito, Jorge; Silvestre, José D.
Abstract: This paper presents a literature review and experimental results on the effect of high incorporation levels of fly ash (FA) and recycled concrete aggregates (RCA), individually and jointly, on the pore system of concrete that remarkably influences its durability. For that purpose, apart from an extensive literature review, three tests were performed, including electrical resistivity (ER) test, which indirectly measures the interconnected porosity of concrete, and water absorption (WA) by capillarity and immersion tests that both depend on the pores number and size but in a different way. A comparison between the experimental results and the literature is also presented to show the main findings and the research needs. The results show that WA increases and ER decreases with increasing incorporation level of RCA, and the opposite occurs with the addition of FA for both tests. The reduction percentage of WA was higher in mixes with both RCA and FA when compared to the sum of reductions in mixes with only RCA or FA. Thus, it is advisable to produce concrete with both mentioned non-traditional materials in terms of WA and ER of concrete. In addition, the benefit of incorporating of FA and RCA in concrete increased even more when superplasticizers was used.